Bringing Derrida’s Deconstructionism into the Classroom: Implications for Pedagogy - Govinda Prasad, Khanal (Siddhajyoti Interdisciplinary Journal, 2025)
Derrida’s theory of deconstruction has drawn the attention of several scholars in the fields of academia including language. While deconstructionism has provided a new lens to viewing reality, the philosophical ideas associated with deconstructionism have tended to be complex to understand particularly to the beginners of language and literary studies. This paper intends to uncover the theoretical underpinnings of deconstruction theory and its enactment in language and pedagogy. The ideas for analysis have been taken from the existing literature through systematic review and have been considered from pedagogical points of view. The analysis shows deconstructionism as a powerful tool to liberate both learners and teachers from centralised and imported hegemonic pedagogical discourses and democratise education through practice of learner autonomy. The pedagogically, recognising the multiplicity of meaning and the use of critical pedagogy can liberate students by promoting critical thinking skills for knowledge construction.